Correlation between Inflammation and Fibrinolysis in Hypertensive Centrally Obese Subjects: A Study on C-Reactive Protein, Plasminogen Activator Inhibitor-1 and Thrombin Activatable Fibrinolysis Inhibitor - Yati Sumiyati; Syakib Bakri; Mansyur Arif (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Hypertension and central obesity are risk factors of cardiovascular disease. Epidemiology studies have shown that these two conditions are closely linked and often occur simultaneously. Inflammation is an underlying pathomechanism in hypertension and obesity. Vascular inflammation is related to coagulation pathway, whereby high level of inflammation increases the risk of atherothrombosis event. The aim of this study was to investigate the correlation between inflammation and fibrinolysis in hypertensive centrally obese subjects compared with hypertensive non obese sbjects.METHODS: This was a cross sectional study conducted in October 2009-June 2010 involving 53 eligible subjects according to the following criteria: men or women aged 30-65 years, had neither diabetes (FPG <126 mg/dL and or OGTT <200 mg/dL) nor CKD (eGFR ≥60 mL/minutes). All subjects were not in an acute inflammation state, had no unspecific infection (hs-CRP ≤10 mg/L), or taking anti-inflammation or anti-hypertensive medication.RESULTS: In this study we found that the levels of hs-CRP (2.636 mg/L vs 1.024 mg/L, p=0.007), PAI-1 (43.58 ng/mL vs. 28.43 ng/mL, p=0.089) and TAFI (12.73 ng/mL vs. 12.19 ng/mL, p=0.479) were respectively higher in hypertensive subjects with central obesity than in hypertensive subjects with no central obesity. In hypertensive centrally obese subjects there was significant positive correlation between hs-CRP and PAI-1 (r=0.491, p=0.001) and TAFI (r=0.312, p=0.0390, meanwhile in hypertensive non-obese subjects significant correlation was found only between hs-CRP and TAFI (r=0.929, p=0.003).CONCLUSIONS: Obesity in hypertensive subjects has higher inflammation state that is correlated with fibrinolysis disruption.KEYWORDS: hypertensive, obesity, hs-CRP, PAI-1, TAFI